Pengaruh Keragaman Produk, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Brandan Donuts Di Pangkalan Berandan - Muhammad Tulus Pekerti; Erni Junaida; Rahmi Meutia (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to determine the effect of product diversity and price on consumer satisfaction of Brandan Donuts in Pangkalan Berandan. This study used a sample of 96 respondents with a minimum purchase frequency of two or more times. The method of analysis used multiple linear regression, t test, F test and coefficient of determination test. The results of this study show Y = 5.484 + 0.612X1 + 0.313X2. The results of the t test show that the product diversity factor has a significant effect on consumer satisfaction of Brandan Donuts in Pangkalan Berandan, price has a significant effect on consumer satisfaction of Brandan Donuts in Pangkalan Berandan. The results of the coefficient of determination test (adjusted R2) obtained a value of 0.556 or 55.6%, this means that product diversity and price variables affect Brandan Donuts consumer satisfaction in Pangkalan Berandan. While the remaining 44.4% is influenced by other variables not examined in this study.